Preparation and characterization of cantaloupe (Cucumis melo L. reticulatus cv. Glamour) fruit powder using foam mat drying and spray drying - Tan, Suet Lin (2020)
Fresh cantaloupe is highly perishable and has a short shelf life. Therefore, drying is used to preserve the quality of cantaloupe fruit in the form of powder that is stable over a longer storage period. The objectives of this research were (i) to evaluate the effect of Arabic gum concentration on the foam properties, drying curve and physicochemical properties of foam mat dried cantaloupe powder, (ii) to evaluate the effect of Arabic gum concentration on physicochemical properties of spray dried cantaloupe powder, (iii) to determine the storage stability of foam mat dried and spray dried cantaloupe powder at room temperature (25 ± 2 °C, 50-70% RH) and accelerated condition (38 ± 2 °C, 90 ± 2% RH) and (iv) to determine the rheological properties of cake icing incorporated with foam mat dried and spray dried cantaloupe powder. Cantaloupe puree (with pulp) was foam mat dried (FMD) using Arabic gum (AG) at different concentrations (0-15%) in cabinet dryer at 55 °C with 3 mm foam thickness. The results showed that cantaloupe pulp with 10% AG gave better foam properties. Page model fitted well the drying curve of FMD of cantaloupe. FMD cantaloupe powder with 10% AG showed better flowability and lower moisture content, hygroscopicity and cohesiveness. For spray drying, cantaloupe juice (without pulp) was dried with AG concentrations (0- 15%) at inlet temperature at 170 °C and outlet temperature at 90 °C. Spray dried (SD) cantaloupe powder produced with 10% AG exhibited the best quality in terms of moisture content, hygroscopicity, hue, water solubility index and total carotenoid content. Therefore, FMD and SD cantaloupe powders with 10% AG were chosen for storage study and application in cake icing. After 6 months of storage, FMD and SD cantaloupe powders were safe to be consumed as the total plate count, yeast and mould and Bacillus cereus had less than 4.40 and 3.38 log CFU/ml, respectively. The degradation of carotenoid content of cantaloupe powders followed first order reaction. A rheological test was done on the cake icing incorporated with 10% AG of FMD and SD cantaloupe powder in the temperature range of 15 to 35 °C. Cake icing incorporated with cantaloupe powders fitted the Power law model and the flow behaviour index (n) of the icings were between 0.104 and 0.156 showed no significant difference (p > 0.05) with the control sample. The icing incorporated with FMD and SD cantaloupe powder showed higher b* value compared to the control sample. FMD and SD cantaloupe powder can be used as a natural colourant and are suitable for confectionery products such as cake icing. The data in this study is useful in food product development and the use of AG could provide more information in foam mat drying using AG as carrier agent.